Hygiene recommendations for regional anesthesia : Updated S1 guidelines of the working group regional anesthesia of the German Society for Anesthesiology - Wiesmann, Thomas; Volk, Thomas; Heinen, Rebecca; Vicent, Oliver; Döffert, Jens; Schulz-Stübner, Sebastian; Geffers, Christine; Kubulus, Christine; Kessler, Paul; Göpfert, Matthias; Wendt, Constanze; Scheithauer, Simone; et al. (Die Anaesthesiologie, 2025)
The updated S1 guideline from the German Society of Anesthesiology and Intensive Care Medicine provides recommendations on hygiene practices for central and peripheral regional anesthesia procedures, aiming to minimize the infection risk for patients. Central to the guideline is the consistent implementation of standardized hygiene measures, with particular emphasis on thorough hand hygiene by the practitioners before and after each procedure. Patient skin preparation should be performed directly with remanent, alcohol-based disinfectants, provided there is no visible contamination. Hair removal is recommended only when necessary, preferably using clippers. For all neuraxial procedures, the use of a face mask, head cover, and sterile gloves is mandatory. In the case of single-shot peripheral nerve blocks, the use of non-sterile disposable gloves may be acceptable depending on the circumstances. Only sterile single-use materials and freshly withdrawn medications from single-dose containers should be used to prevent crosscontamination. In ultrasound-guided procedures, the use of a sterile probe cover and thorough disinfection of the ultrasound transducer before and after use are obligatory. For indwelling regional anesthesia catheters, the insertion site must be inspected daily; dressing changes should be performed only when infection is suspected or when there is an evident clinical indication. Catheter tunneling and the use of chlorhexidine-containing dressings may contribute to reducing bacterial contamination. If signs of infection occur, targeted diagnostics and infection-specific treatment should be initiated, according to the severity of the clinical presentation. Additionally, the guideline recommends the introduction of hygiene bundles, standardized procedural kits, and regular staff training. These measures should be subject to continuous evaluation and optimization via structured monitoring and benchmarking. All recommendations must be adapted to local conditions and institution-specific hygiene protocols.